Applied fluid mechanics - Mott, Robert L.; Untener, Joseph A. (Always learning.., 2016)
"Now in full color with an engaging new design, Applied Fluid Mechanics, Seventh Edition, is the fully updated edition of the most popular applications-oriented approach to engineering fluid mechanics. It offers a clear and practical presentation of all basic principles of fluid mechanics (both statics and dynamics), tying theory directly to real devices and systems used in mechanical, chemical, civil, and environmental engineering. The 7th edition offers new real-world example problems and integrates the use of world-renowned PIPE-FLO® software for piping system analysis and design. It presents new procedures for problem-solving and design; more realistic and higher quality illustrations; and more coverage of many topics, including hose, plastic pipe, tubing, pumps, viscosity measurement devices, and computational fluid mechanics. Full-color images and color highlighting make charts, graphs, and tables easier to interpret organize narrative material into more manageable "chunks," and make all of this text's content easier to study."--Publisher's website.